If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7q + -18 = 3 Reorder the terms: -18 + 7q = 3 Solving -18 + 7q = 3 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 7q = 3 + 18 Combine like terms: -18 + 18 = 0 0 + 7q = 3 + 18 7q = 3 + 18 Combine like terms: 3 + 18 = 21 7q = 21 Divide each side by '7'. q = 3 Simplifying q = 3
| (2x/3)-1 | | 2*2x-3=65 | | x^2-4x+4-49=0 | | 22x-x= | | 2*2x+3-65=0 | | (2+i)-(6-2i)= | | 2x^2+3-65=0 | | 43+x-19=36 | | 80+x-68=32 | | x^2-6x+-49=0 | | -2(4x-2-4)=5(x+2) | | 2n-13=17 | | 72+x-35=49 | | -2(4x-2)=5(x+1) | | 8x+3=7x+6 | | (5-2x)/x=1/4 | | 6b^2-10=14 | | x^2+2c+24=0 | | x+39=7 | | 8sinx-3=0 | | 3x-2-2x=1+2x+8 | | (2x-5)1/2=7 | | 5(3x-2)=2(x+2) | | 2(f-4)+8-4h=-3 | | 3x^2-118x+899=0 | | y=4x(2x+3)+1 | | T-12/6=4/3 | | 11x+6=8x+9 | | X*2x+3-65=0 | | 3(3x+5)=3x-1 | | 2x^2-12x+25=y | | -8x-4x=8-1 |